Predictors of breastfeeding self-efficacy in pregnant adolescents - Funda Ozdemir; Seda Karaçay Yıkar; Evşen Nazik (Faculty of Medicine, Universitas Trisakti, 2022)
BackgroundBreastfeeding is critical for infant health and development globally. Current knowledge and attitude of future parents will significantly influence breastfeeding practices. The study was conducted to determine the levels and determinants of breastfeeding self-efficacy among primiparous and secundigravid adolescents. MethodsA cross-sectional study was performed involving 54 primiparous and secundigravid adolescents in antenatal clinics of hospitals affiliated to the Ministry of Health in Adana, Turkey. They were aged between 16 and 19 years, had a single living fetus, did not have pregnancy complications, were in their third trimester of pregnancy, attended an antenatal clinic, and agreed to participate in the study. Data were collected using a Personal Information Form and the Antenatal Breastfeeding Self-Efficacy Short Form Scale (BSES-SF). Kruskal-Wallis variance analysis, Mann Whitney U and multiple linear regression analysis test were used to analyze the data. ResultsMean age of the pregnant adolescents was 18.28 ± 0.79 years, and 31.5% had primary education, 96.3% were not working, 55.6% lived in a nuclear family, and 51.9% had not received breastfeeding education. The total BSES-SF mean score was 55.37 ± 12.84. Breastfeeding education has a statistically significant effect on breastfeeding self-efficacy of pregnant adolescents (p<0.05). Regular antenatal care, breastfeeding training status, breastfeeding education source variables and breastfeeding self-efficacy variable of women significantly predicted negatively (p<0.05). ConclusionsBreastfeeding education source was the most influential predictor variable of BSES. There is a need for nursing initiatives to enhance the adolescents’ antenatal breastfeeding self-efficacy levels.